The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1123/jtpe.24.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among Dispositional Ability Conceptions, Intrinsic Motivation, Perceived Competence, Experience, and Performance

Abstract: This study was designed to explore the relationships among individuals’ dispositional ability conceptions, intrinsic motivation, experience, perceived competence, persistence, and performance. Participants practiced a novel task, completed surveys before instruction and after practicing the task, and completed a skill test. The results indicated that participants with higher levels of entity ability conceptions were likely to exert less effort and be less intrinsically motivated during practice. Participants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
1
17

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 21 publications
3
51
1
17
Order By: Relevance
“…A positive and signifi cant correlation between the entity view of ability and gift and between the improvement and learning factors was found. To the contrary, there was a signifi cant and negative relationship between entity belief and incremental beliefs (improvement and learning) and between the factor of gift and improvement, which is similar to the fi ndings obtained by Biddle et al (2003) and Li et al (2005). On the other hand, self-determined motivation correlated positively with the incremental beliefs of improvement and learning and negatively with the beliefs that ability is stable and related to gift, which is consistent with previous works (Li et al, 2005).…”
Section: Structural Equation Modelsupporting
confidence: 90%
See 2 more Smart Citations
“…A positive and signifi cant correlation between the entity view of ability and gift and between the improvement and learning factors was found. To the contrary, there was a signifi cant and negative relationship between entity belief and incremental beliefs (improvement and learning) and between the factor of gift and improvement, which is similar to the fi ndings obtained by Biddle et al (2003) and Li et al (2005). On the other hand, self-determined motivation correlated positively with the incremental beliefs of improvement and learning and negatively with the beliefs that ability is stable and related to gift, which is consistent with previous works (Li et al, 2005).…”
Section: Structural Equation Modelsupporting
confidence: 90%
“…These results have been corroborated by Biddle et al (2003) and Wang and Biddle (2001). In this sense, Li et al (2005) found that intrinsic motivation was positively predicted by incremental beliefs.…”
Section: Structural Equation Modelsupporting
confidence: 55%
See 1 more Smart Citation
“…Behavioural correlates were most often a measure of physical activity or a measure of task performance. Other behavioural correlates included selfregulation, self-handicapping, reactions to success and failure, and effort (e.g., W. Li, Lee, & Solmon, 2005;Y. Ommundsen, 2001bY.…”
Section: Qualitative Synthesis Of the Evidencementioning
confidence: 99%
“…Los resultados mostraron que la creencia implícita incremental sobre la habilidad deportiva predijo positivamente el índice de autodeterminación, mientras que la creencia implícita de entidad sobre la habilidad lo predijo negativamente. En esta misma línea, diversos estudios (Li, Lee, y Solmon, 2005;Ntoumanis y Biddle, 1999;Sarrazín, Vallerand, Guillet, Pelletier, y Cury, 2002;Sicilia et al, 2011) coinciden en la relación entre un contexto educativo-deportivo en el que se promueve una creencia implícita incremental sobre la habilidad deportiva (valoración del proceso y la superación personal), con una mayor motivación autodeterminada en los estudiantes. Contrastando la segunda hipótesis, se encontró que el índice de autodeterminación predijo negativamente la percepción de discriminación y positivamente la percepción de igualdad de trato.…”
Section: Discussionunclassified